2013
DOI: 10.1186/1756-0500-6-279
|View full text |Cite
|
Sign up to set email alerts
|

Coronary calcium scoring: are the results comparable to computed tomography coronary angiography for screening coronary artery disease in a South Asian population?

Abstract: BackgroundThe need of having feasible screening tools like Coronary Calcium Scoring (CCS) and CT Coronary Artery (CTCA) for Coronary Artery Disease (CAD) has become paramount. We aimed to evaluate the accuracy of CCS in determining the degree of stenosis of coronary vessels as compared to that determined by CTCA in a South Asian population.MethodsA retrospective study was conducted at The Aga Khan University Hospital. A total of 539 patient records were reviewed who had undergone CCS and CTCA between 2008 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…Thirdly, there are few studies that CACS is useful for re-stratification for cardiovascular events in Asian population. However, there are some studies performed in Asian population regarding the predictive value of high CACS for cardiovascular mortality compared to low CACS, providing the evidence of CACS as the reliable tool for screening in Asians [35,36]. Fourth, our study has another limitation that we do not have the follow up data for these study population.…”
Section: Discussionmentioning
confidence: 68%
“…Thirdly, there are few studies that CACS is useful for re-stratification for cardiovascular events in Asian population. However, there are some studies performed in Asian population regarding the predictive value of high CACS for cardiovascular mortality compared to low CACS, providing the evidence of CACS as the reliable tool for screening in Asians [35,36]. Fourth, our study has another limitation that we do not have the follow up data for these study population.…”
Section: Discussionmentioning
confidence: 68%
“…This study was conducted before coronary artery calcium score measurement became routine and used a semi‐quantitative measure of CAD atheroma burden (Gensini score) that shows a weak correlation ( r = 0.30) with coronary calcium scores . However, in general calcium scores correlate with severity of atheromatous disease measured on CT coronary angiography in Pakistani populations suggesting that this relationship is still relevant to modern practice.…”
Section: Discussionmentioning
confidence: 99%
“…[46,47] One report from a large urban teaching hospital in Pakistan examined the correlation between CAC scores and coronary luminal obstruction based on CT angiography. [47] Consistent with findings from cohorts in high-income countries, the authors found that low CAC scores (< 10) were associated with a low frequency of obstructive CAD while a majority of subjects (74%) with CAC scores exceeding 400 had severe coronary stenosis. [48] Another study from India found that presence of CAC in an asymptomatic population was associated with traditional atherosclerotic risk factors, such as age, hypertension and diabetes mellitus.…”
Section: Atherosclerotic Cardiovascular Diseasementioning
confidence: 99%